Jakarta Under Water: The 2007 Flood and The Debate on Jakarta’s Future Water Infrastructure - Anto Mohsin (Department of Urban and Regional Planning, Diponegoro University, 2015)
This paper examines the debate in the wake of the 2007 flood in Jakarta, the biggest one to occur in the city’s history. By analyzing textual sources both online and in the archives as well as interviews with several actors in the debate, I demonstrate that a new socio-political condition in Indonesia facilitated a vibrant discourse in the wake of a so-called “natural disaster.” In a democratizing society such as Indonesia, state actors no longer monopolized the social production of a “risk object” or a source of danger or harm. I show that the Indonesian public, who participated in the debate, shaped “networks of risk objects” either by “emplacing” a risk object (i.e. defining an entity as an object and linking it to a potential harm) or by “displacing” it (i.e. challenging the existence of a risk object or delinking it from a putative danger) (Hilgartner, 1992). These non-state actors managed to insert themselves into a sphere once dominated by the technocrats, in large part because the press was no longer controlled by the state. In doing so, they exposed the messiness and vulnerability of the city’s water management system. The “risk objects” they identified to run the whole gamut of entities that make up the entire Jakarta’s water management socio-technical system, which includes water technologies, laws, practices, institutions, conditions, policies, and the environment.